Blockchain Research a Scientometric Assessment of Global Literature during 2010 to 2018 - Gupta, B. M.; Dhawan, S. M. (DESIDOC Journal of Library & Information Technology, 2020)
The paper analyzes global publications in blockchain research on a series of quantitative and qualitative indicators, using Scopus database. Blockchain research published a total of 4629 research publications in 9-year period during 2010-18. The publications registered a fast growth of 150.24 per cent and registered average citation impact per paper of 5.04. The paper profiles most productive countries, organisation, authors and journals on select bibliometric indicators. The top 29 highly-cited papers in this area are also analysed.